Assessment of climatic trend of air temperature at the earth surface in the context of stable development (case of Gyumri city) - Margaryan, Varduhi Gurgenovna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Formulation of the problem. The study and assessment of air temperature fluctuations, especially in conditions of expected climate change, is of particular relevance and haste. At the same time, the assessment of temporary changes in air temperature is important as a guarantee of stable development and a long-term economic development. The purpose of the article. The purpose of this work is to find out, analyze and evaluate the patterns of the dynamic changes in air temperature in Gyumri city. To solve this problem, the results of actual observations of the air temperature of the Gyumri weather station, stored at the Ministry of Emergency Situations of the Republic of Armenia «Service for Hydrometeorology and active influence on atmospheric phenomena» have been collected, refined and analyzed. Methods. In the course of research we analyzed and clarified appropriate literary sources, using mathematical-statistical, extrapolation, complex, analyze and correlation methods. Results. A multifactorial correlation relationship was obtained between the average annual air temperature and its absolute maximum and minimum values of Gyumri city. A close correlation was also obtained between the average annual air temperature and its absolute maximum and minimum values of Gyumri city, between the average annual and extreme values of the surface air temperature and the absolute maximum and minimum values of the soil surface of Gyumri city. This makes it possible to calculate the value of any temperature characteristic, while having the other one. Note that in winter the average air temperature values do not differ much from the average soil surface temperature values. This difference grows and reaches its maximum in summer (July – August). As a result of the research, it turned out that according to the actual data on the air temperature in Gyumri city, there was a tendency for the average annual values and absolute maximum of the air temperature to rise, while the absolute minimum values showed a downward trend (in the absolute sense). That is, in the study area in the warm season, an increase in aridity is expected on climate drainage, and in the cold season – a softening. In the work we tried to define the monthly average values of air temperature in Gyumri in 2030, 2070, 2100, using the extrapolation method. The result shows that if the changing process continues, the annual average values of air temperature will increase with comparison to current normal: in 2030 – 0.09 ºC (1.37 %), in 2050 – 0.27 ºC (4.12 %), in 2070 – 0.48 ºC (7.32 %), in 2100 – 0.85 ºC (13 %). This pattern is also characteristic of other regions of the republic. Therefore, it is necessary to implement integrated measures to adapt to the effects of air temperature changes and take this into account when working out programs for social, environmental and economic development.